TRANSAKSI DERIVATIF LINDUNG NILAI (HEDGING) PADA BANK BUMN - Utamie, Dara Nida (Nusantara Hasana Journal, 2022)
This study aims to determine the application of hedging derivative transactions at state-owned banks in Indonesia. The research method used in this study is a qualitative approach with content analysis. This study uses the financial statements of 2020. The results show that the state-owned banks, namely BNI, BRI, BTN and Mandiri, are using derivative instruments to hedge. The derivative transactions in question are swaps, spots, forward contracts and options. In addition, the use of derivative instruments in banking is used as risk mitigation. The efforts carried out by state-owned banks are included on a large scale which have more potential to use derivative instruments. The cost of using derivatives is considered a variable cost and usually large-scale companies such as state-owned enterprises have more funds to bear these costs and consider the economic benefits.